2008
DOI: 10.1109/ccece.2008.4564770
|View full text |Cite
|
Sign up to set email alerts
|

A new hardware architecture for sampling the exponential distribution

Abstract: Hardware acceleration in high performance computing context is of growing interest, particularly in the field of Monte Carlo methods where the resort to FPGA technology enhances execution speed by several orders. For this purpose, a particular attention has been given lately to hardware-based non-uniform random variate generators. In this paper we present both a hardware-dedicated decision tree technique for the generation of exponential variates and a derived architecture implemented in FPGA. The proposed des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Table I summarizes the major GVG and EVG architectures reviewed in this paper. As one can see, the design in [20] compares well with all the major designs even if it uses multiple LFSRs. Moreover, it doesn't make use of any multiplier and surpasses the designs in [16] in the effective area and BRAMs occupation.…”
Section: B Hardware Evgmentioning
confidence: 86%
See 4 more Smart Citations
“…Table I summarizes the major GVG and EVG architectures reviewed in this paper. As one can see, the design in [20] compares well with all the major designs even if it uses multiple LFSRs. Moreover, it doesn't make use of any multiplier and surpasses the designs in [16] in the effective area and BRAMs occupation.…”
Section: B Hardware Evgmentioning
confidence: 86%
“…An empirical analysis [13] showed that multiple (let us say k) w-bit LFSRs can be used in either a serial or parallel topology (the latter requires appropriate initial seeds) to form a PRNG with an enhaced random behaviour. This approach was successfully used in [19] and [20] but our implementation results showed a greedy ressource occupation: for instance, on Virtex II-Pro FPGA technology, the parallel topology (w = 32 and n = k · w = 1008) translates into an occupation of more than 1, 000 slices.…”
Section: A Hardware Implementation Of Uniform Prngmentioning
confidence: 99%
See 3 more Smart Citations